Concerning rather modern organizational innovations in the system of physical education of student youth. - Сутула, Василь Опанасович; Луценко, Лариса Сергіївна; Булгаков, Олексій Ігорович; Дейнеко, Альфія Хамзіївна; Сутула, Анастасія Василівна; Шутєєв, Вячеслав Вадимович (Slobozhanskyi Herald of Science and Sport, 2016)
Sutula V., Lutsenko L., Bulgakov A., Deyneko A., Sutula A., Shuteev V. Purpose: studying of attitude of students to the existing system of physical education in higher educational institutions of Ukraine and an assessment of possible consequences of implementation of the order of MES of January 26, 2015 No. 47 and the corresponding explanations and recommendations to it which are stated in the letter of MES No. 1/9-1126 of 13.03.2015. Material & Methods: the poll of students of 1–4 courses (n=757) of one of the faculties of Law University named after Yaroslav the Wise (NLU) was conducted for the achievement of the stated purpose. Health cards of students, log-books of educational work on physical training of students, log-books of work of sports and improving sections were also analyzed. Results: interest in classes by physical exercises decreases at the vast majority of students during training in higher educational institutions. 88,6% of students note a need of carrying out classes on discipline "Physical education" for higher educational institutions. The majority of them (80,2%) will choose discipline "Physical education" if it will be optionally, and 71,9% understand that they need to be engaged in physical exercises 4-6 hours per week for maintenance of the appropriate level of their physical health. Conclusions: the positive result of functioning of the existing system of physical training of student’s youth will be shown that interest in classes by physical exercises decreases at the vast majority of students during training. The effective modernization of the system of physical training of student youth is possible, first, due to use of the existing gender distinctions in interests in classes by physical exercises at students. Secondly, due to properly organized classes with the students who are for health reasons to preparatory (10,9%), special (19,1%) medical groups and MPC groups (3,4%). The considerable issues will appear with visit of such classes by students in case of a removal of classes on physical education of students in the department of facultative classes.